Implementasi Pembelajaran Station Rotation Mapel PJOK pada Materi Aktivitas untuk Kebugaran terhadap Tingkat Kelincahan Siswa - Mauludiyah, Novi; Muhammad, Heryanto Nur; Wibowo, Sapto (EduInovasi: Journal of Basic Educational Studies, 2024)
Physical Education, Sports and Health (PJOK) is an integral part of the education system that provides knowledge and skills in the field of physical activity and sports. Station Rotation learning is a class-based learning method that is a driving model type, which requires students to take turns completing the program. Tactical Approach learning is a planned process to perfect. game appearance. which it contains. combiner. elements of tactical circumstances. and implementation of expertise. The aim of this research is to analyze the implementation of station rotation learning and Tactical Approach learning in the PJOK subject, activity material for fitness in class VII students at SMPN I Dringu. . It is hoped that the results of this research can be used by practitioners as evaluation material for science in the field of science that has been carried out with the benefits of learning the Station Rotation and Tactical Approach models. This research uses quantitative research with a quasi-experimental method (Quasi experiment) with the design of this research using Randomized Control group pretesh-posttest Design. The analysis used is average (mean), standard deviation, normality test and T test. The results of this research after being tested with Paired Samples Statistics and T Test were that there was a significant influence on the learning of the Station Rotation and Tactical Approach models with a mean of 14.78 at the pre-test and 13.32 at the post-test for male students. With a mean of 18.11 during the pre-test and 16.98 during the post-test for female students, a mean of 15.41 during the pre-test and 14.26 during the post-test for male students and a mean of 17.98 during the pre-test and 15.98 during the post-test for male students. .81 during the post test for female students